#NeverAgain : preventing gun violence - Thomas, Rachael L. (#Movements., 2020)
Briefly investigates the history of the anti-gun violence and "#NeverAgain" movement, highlighting how social media and the use of hashtags helped drive the movement forward. Includes a timeline and glossary.